Serovars and antimicrobial resistance of non-typhoidal Salmonella from human patients in Shanghai, China, 2006–2010. (10th July 2013) - ZHANG, J.; JIN, H.; HU, J.; YUAN, Z.; SHI, W.; RAN, L.; ZHAO, S.; YANG, X.; MENG, J.; XU, X.
SUMMARY: We conducted a retrospective study on non-typhoidal Salmonella isolates from patients with diarrhoea in Shanghai, China, 2006–2010. A total of 1484 isolates of 70 Salmonella serovars were recovered from about 18 000 stool specimens. Serovars Enteritidis and Typhimurium were the most prevalent with isolation rates of 27·6% and 25·5%, respectively. The majority (1151, 77·6%) of the isolates were resistant to at least one antimicrobial, and 598 (40·3%) to more than three antimicrobials. Approximately half (50·9%) of the isolates were resistant to nalidixic acid and other resistance rates were sulfisoxazole (47·9%), streptomycin (37·6%), ampicillin (31·3%) and tetracycline (30·5%). Co-resistance to fluoroquinolones and the third- and fourth-generation cephalosporins was also identified.